Burden of informal caregivers of dependent elderlies in the community in small cities - Marines Aires; Ana Cláudia Fuhrmann; Duane Mocellin; Fernanda Laís Fengler Dal Pizzol; Laura Franco Sponchiado; Carla Regina Marchezan; Carla Cristiane Becker Kottwitz Bierhals; Carolina Baltar Day; Naiana Oliveira dos Santos; Lisiane Manganelli Girardi Paskulin (Universidade Federal do Rio Grande do Sul, 2020)
ABSTRACT Aim: To analyze sociodemographic factors and aspects of care related to the burden of informal caregivers of dependent elderlies in the community. Methods: A cross-sectional study with 125 caregivers. Data collection was carried out in municipalities of the Northwest of Rio Grande do Sul through a structured interview in 2017 and 2018. The Caregiver Burden Inventory was used. The Pearson or Spearman correlation coefficients and t-student test or Analysis of Variance (ANOVA) were done. For the multivariate analysis, Linear Regression was used. Results: Most caregivers were female (73.6%), married (55.2%) and daughters (68.0%). The variables that showed a statistically significant relationship with burden were: caregiver age (p = 0.039), education (p = 0.001), time devoted to care (p = <0.001), kinship degree (p = 0.001), living with the elder (p <0.001), using their income (p = 0.001) and female gender (p = 0.017). Conclusion: Women caregivers, with less education, who spend more time in weekly care and lived with the elder presented higher burden.